Public Attitudes Toward Legal Abortion, Euthanasia, Suicide, and Capital Punishment: Partial Evidence of a Consistent Life Ethic. (March 2017) - Trahan, Adam
Recent research suggests that public attitudes toward capital punishment are fundamentally value expressive rather than instrumental. This study explores the value-expressive basis of capital punishment attitudes by analyzing the relationships between various domains of life and the law. Logistic regression of data from the 1972–2012 cumulative data file of the General Social Survey was used to analyze whether composite variables for opposition to legal abortion, euthanasia, and suicide could predict capital punishment attitudes. Findings show that main effects of opposition to legal abortion, suicide, and euthanasia increased the odds of opposing capital punishment. Among 3 two-way interaction terms, only opposition to suicide and euthanasia was significant, and it was associated with increased support for capital punishment rather than opposition. These findings lend qualified support to the consistent life ethic framework and value-expressive basis of capital punishment attitudes.